WAYS OF DEVELOPMENT OF CREATIVE THINKING OF JUNIOR SCHOOLCHILDREN (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
At primary school age, thinking, due to the inclusion of the child in educational activities aimed at mastering the system of scientific concepts, rises to a higher level. The development of critical thinking in younger students contributes to the proper organization of educational activities, the development of theoretical concepts by children.